New technique for in-situ measurement of backscattered and secondary electron yields for the calculation of signal-to-noise ratio in a SEM - SIM, K. S.; WHITE, J. D. (2005)
The quality of an image generated by a scanning electron microscope is dependent on secondary emission, which is a strong function of surface condition. Thus, empirical formulae and available databases are unable to take into account actual metrology conditions. This paper introduces a simple and reliable measurement technique to measure secondary electron yield (delta) and backscattered electron yield (eta) that is suitable for in-situ measurements on a specimen immediately prior to imaging. The reliability of this technique is validated on a number of homogenous surfaces. The measured electron yields are shown to be within the range of published data and the calculated signal-to-noise ratio compares favourably with that estimated from the image.